Women's Resistance Against Sexual Violence in The Keeping Room Movie (2014) - Ganindra Ahmad Altamir (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
This article attempts to analyze sexual violence against women and women's resistance against sexual violence in a movie entitled The Keeping Room by Daniel Barber using Johan Galtung's theory of violence triangle to reveal the roots of sexual violence against women, and James Scott's theory of resistance to explain women's resistance against sexual violence which related to the rise of sexual violence cases against women in the emergency situation of sexual violence at this time. Johan Galtung's theory of violence triangle sees the phenomenon of sexual violence against women as a form of direct violence, structural violence, and cultural violence. Meanwhile, James Scott's resistance theory sees women's resistance to sexual violence in two forms, namely public resistance and vague resistance. The author uses descriptive-qualitative methods and textual analysis to explain sexual violence and women's resistance depicted in the scenes and dialogues between characters in the movie. The results of analysis show that the root of sexual violence against women is patriarchal structure in the form of direct violence, structural violence, and cultural violence that causes the relations between men and women become unequal and subordinates women’s position in society. Meanwhile, women's resistance against sexual violence is divided into two, namely armed resistance as public resistance and camouflage as disguised resistance. Keywords: Sexual Violence, Resistance, Patriarchy